HIDROLISIS KONSENTRAT PROTEIN BUNGKIL NYAMPLUNG (Callophyllum inophyllum L.) RENDAH MINYAK DAN EVALUASI AKTIVITAS ANTIOKSIDANNYA - , Zayyini Nahdlah, Dr. Ir. Chusnul Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nyamplung protein concentrate was produced from defatted nyamplung flour seed and used as starting material for producing protein hydrolysate using bromelin as biocatalyst. The objecttive of this study was to evaluate the effect of both enzym concentration and time of hydrolysis on antioxidant activities of nyamplung protein hydrolysates. The result showed that increasing two time of enzym concentration could significantly increase the degree of (1.25 folds). The hydrolyzed protein using bromelin for 4 h resulted in significantly increase in DH. An increase in reaction time did not have significant effect on DH. Total phenol content increased from 21.25 mg/g (db) to 64.96 mg/g after 8 h hydrolysis. The result indicated that the antioxidant activitiy of protein hydrolysates were related to the increase in time of hydrolysis and total fenol content. IC50 DPPH value of defatted nyamplung protein concentrate, defatted nyamplung protein hydrolysate after 1 h and 8 h reactions were 150.51, 69.72 and 33.80 mg/ml, respectively. There wais no significant different compared with ascorbic acid (35.86 mg/ml).